Secondary Metabolites from Some Species of Albizzia: A Review (Bangladesh Pharmaceutical Journal, 2016)
This review covers the secondary metabolites reported from five species of Albizzia. A total of fifty chemical constituents have been documented from A. anthelmintica, A. chinensis, A. julibrissin, A. lebbeck and A. myriophyla. Most of the phytoconstituents have been reported from A. julibrissin and A. lebbeck.Bangladesh Pharmaceutical Journal 19(1): 1-8, 2016